2002
DOI: 10.2486/indhealth.40.149
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Length of Employment and Working Conditions with Neck, Shoulder and Arm Pain among Nursery Scool Teachers.

Abstract: A cross-sectional questionnaire study was carried out on nursery school (NS) teachers in public nursery schools in N city in Japan to determine the magnitude of associations of probable risk factors with neck, shoulder, and arm pain, adjusting for potential confounders in logistic regression models. Of 1438 subjects, responded to the questionnaire, 959 NS teachers in charge of a separate or mixed group of children were subjected to analyses. Prevalence of neck and/or shoulder pain was 33.6%-35.4% in NS teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
2
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 20 publications
5
36
2
4
Order By: Relevance
“…This speculation is partly supported by Ono et al who compared the sick leave statistics of sewing machine operators on full-time schedules with that of part-time operators. [13] As per the Table 4 study shows knee and thigh pain occur in teachers due to prolong standing for several hours in school and repetitive stair climbing in school during working hours. Overall physical work load seem to be the most important risk factor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This speculation is partly supported by Ono et al who compared the sick leave statistics of sewing machine operators on full-time schedules with that of part-time operators. [13] As per the Table 4 study shows knee and thigh pain occur in teachers due to prolong standing for several hours in school and repetitive stair climbing in school during working hours. Overall physical work load seem to be the most important risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Activities of sustained sitting in front of computer, standing up teaching in class, repetitively, overhead writing on the board are also unsafe act found in teachers. [13] Neck pain among the school teachers is mainly due to awkward posture -sitting with poking chin which induce considerable load on the posterior structures of spine, leading to increased tension on non-contractile structures and posterior cervical structures. [14] Table 4 shows the prevalence of upper back and lower back pain is 29.97% and 49.92%, respectively, for the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allen et al 50) reported no relationship between voluntary overtime ranging up to 60+ h per week and MS injuries in workers at a truck manufacturing plant. One 51) of the four studies examining symptoms reported a significant increase, while the other three were not significant [52][53][54] . Bourdouxhe and Toulouse 52) theorized their findings might have been influenced by lack of a comparison group working 40 h per week, since almost all of their film technicians worked very long hours.…”
Section: Long Work Hoursmentioning
confidence: 99%
“…On the other hand however, other research has suggested that LBP is not related to hormonal fluctuations during the menstrual cycle nor to the use of Oral Contraceptives (OC) 14) . Back pain is known to be an increasingly common problem for the Japanese workforce 15) and has been studied epidemiologically in a variety of occupational fields such as construction workers 16) , taxi drivers 17) and school personnel [18][19][20] . The Japanese health care workforce is also known to suffer LBP, with previous research revealing high rates of musculoskeletal disorders among hospital nurses 6,8,21) and nursing home workers [22][23][24] .…”
mentioning
confidence: 99%